2021
DOI: 10.1016/j.anai.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Tuft cells in the pathogenesis of chronic rhinosinusitis with nasal polyps and asthma

Abstract: Tuft cells are a type of rare epithelial cell present in the respiratory and intestinal tracts, among other locations in humans, rodents, and reptiles.In addition to other functions, tuft cells use components of the taste transduction system to survey the extracellular environment and play a role in pathogen defense by stimulating neighboring ciliated epithelial cells to secrete antimicrobial products.The dominant epithelial source of interleukin-25 and an important source of cysteinyl leukotrienes in the airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 105 publications
0
14
1
1
Order By: Relevance
“…This body of work supports vaginal epithelial cells to be the key source of IL-33-mediated type 2 immunity in the FGT during co-infection. Recent studies have identified myeloid sources of IL-33 to play roles in downregulating mucosal inflammation (Hung et al, 2020a(Hung et al, , 2020bJackson et al, 2020;Sell et al, 2020). The findings we present here do not currently suggest a role for cells other than epithelial cells as a contributing source of IL-33.…”
Section: Discussioncontrasting
confidence: 71%
“…This body of work supports vaginal epithelial cells to be the key source of IL-33-mediated type 2 immunity in the FGT during co-infection. Recent studies have identified myeloid sources of IL-33 to play roles in downregulating mucosal inflammation (Hung et al, 2020a(Hung et al, , 2020bJackson et al, 2020;Sell et al, 2020). The findings we present here do not currently suggest a role for cells other than epithelial cells as a contributing source of IL-33.…”
Section: Discussioncontrasting
confidence: 71%
“…SCCs appear to be regulated by type II cytokines like IL-13 or IL-4 and/or exposure to fungal metabolites. (16) Thus, SCCs may only be prevalent in the nose of CRS patients with nasal polyps (CRSwNP), a subset of CRS driven by type II cytokines, (70) or in patients with allergic fungal sinusitis. CRS without ( sans ) nasal polyps (CRSsNP) is most often characterized by other inflammatory profiles.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are also referred to as “brush cells.” (15) SCCs regulate several responses, including IL-25 and/or acetylcholine release to activate epithelial inflammation or trigger mucus clearance, respectively. (16, 17) In the nose, they also regulate secretion of antimicrobial peptides like defensins. (13, 18) SCC activation of antimicrobial peptide secretion is reduced by activation of the sweet taste receptor (taste family 1 receptor) subunits T1R2 and T1R3 via ASL glucose (13) or sweet bacterial D-amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous ligand of nAchR, acetylcholine (Ach), is a classic neurotransmitter synthesized by Choline Acetyltransferase (ChAT) in cholinergic neurons, as well as in immune cells and epithelial cells, such as brush/tuft cells (Kummer & Krasteva-Christ, 2014; Wessler & Kirkpatrick, 2008). Such cells orchestrate type 2 inflammatory responses (O’Leary et al, 2019; Sell et al, 2021), mucociliary clearance (Perniss et al, 2020) and limit biliary inflammation (O’Leary et al, 2022; O’Leary et al, 2019). How Ach influences homeostasis of barrier epithelia and how disease-associated nAchR variants perturb epithelial function remains mostly unclear.…”
Section: Introductionmentioning
confidence: 99%